Α-Lipoic Acid-Plus Ameliorates Endothelial Injury by Inhibiting the Apoptosis Pathway Mediated by Intralysosomal Cathepsins in an In Vivo and In Vitro Endothelial Injury Model. (12th April 2022) - Wang, Yang; Bao, Dejun; Dong, Yongfei; Wei, Xiangpin; Yu, Jian; Niu, Chaoshi
Abstract : α -Lipoic acid-plus (LAP), an amine derivative of α -lipoic acid, has been reported to protect cells from oxidative stress damage by reacting with lysosomal iron and is more powerful than desferrioxamine (DFO). However, the role of LAP in experimental carotid artery intimal injury (CAII) has not yet been well investigated. Therefore, we sought to uncover the role and potential endovascular protective mechanisms of LAP in endothelial injury. In vitro, oxyhemoglobin (OxyHb) stimulation of cultured human umbilical vein endothelial cells (HUVECs) simulated intimal injury. In vivo, balloon compression injury of the carotid artery was used to establish a rat CAII model. We found that the protein levels of cathepsin B/D, ferritin, transferrin receptor (TfR), cleaved caspase-3, and Bax increased in the injured endothelium and HUVECs but were rectified by DFO and LAP treatments, as revealed by western blotting and immunofluorescence staining. Additionally, DFO and LAP decreased oxidative stress levels and endothelial cell necrosis of the damaged endothelium. Moreover, DFO and LAP significantly ameliorated the increased oxidative stress, iron level, and lactic dehydrogenase activity of HUVECs and improved the reduced HUVEC viability induced by OxyHb. More importantly, DFO and LAP significantly reduced mitochondrial damage and were beneficial for maintaining lysosomal integrity, as indicated by acridine orange (AO), Lyso-Tracker Red, JC-1, and ATPB staining in HUVECs. Finally, LAP might offer more significant endovascular protective effects than DFO. Our data suggested that LAP exerted endovascular protective effects by inhibiting the apoptosis signaling pathway mediated by intralysosomal cathepsins by reacting with excessive iron in endothelial lysosomes after intimal injury.